Failure Analysis of Spinning Roll Shaft in Cone Plate Formation Using Finite Element Method (FEM) - Muhammad arif nur huda; Galuh Zuhria Kautzar; Eko Yudiyanto (Evrimata: Journal of Mechanical Engineering, 2025)
This study of the failure of spinning roll shafts used in cone plate formation, caused by uneven stress distribution due to suboptimal geometric design. The aim of this research is to analyze the root causes of shaft failure and optimize its design using Finite Element Method (FEM). The method employed involves simulating the spinning roll shaft with various geometric dimensions, such as diameter and fillet radius, to evaluate stress distribution and identify potential failure points. The results indicate that maximum stress occurs at the shaft diameter transition and fillet radius areas, leading to stress concentration, which can cause premature failure. Design improvements, such as increasing the fillet radius and enlarging the transition diameter, significantly reduced maximum stress and enhanced the shaft's safety factor. In conclusion, the research demonstrates that shaft failure is primarily caused by geometric design flaws resulting in excessive stress concentration rather than material quality. Modifying the geometry, especially the fillet radius and diameter transition, can improve the reliability and lifespan of the shaft, thereby reducing the risk of failure in cone plate spinning processes.